2019
DOI: 10.1111/dom.13861
|View full text |Cite
|
Sign up to set email alerts
|

Short‐term fully closed‐loop insulin delivery using faster insulin aspart compared with standard insulin aspart in type 2 diabetes

Abstract: We evaluated the efficacy and safety of short‐term fully closed‐loop insulin delivery using faster versus standard insulin aspart in type 2 diabetes. Fifteen adults with insulin‐treated type 2 diabetes underwent 22 hours of closed‐loop insulin delivery with either faster or standard insulin aspart in a double‐blind randomized crossover design. Basal‐bolus regimen was replaced by model predictive control algorithm‐directed insulin delivery based on sensor glucose levels. The primary outcome was time with plasma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 21 publications
3
12
0
1
Order By: Relevance
“…The inferior postprandial glucose control and higher insulin doses after breakfast compared with lunch and dinner suggest that breakfast poses greater challenges to automated systems. A similar pattern with higher excursions after breakfast compared with lunch was observed in previous work exploring fully closed‐loop insulin delivery in adults with type 2 diabetes in a controlled research setting 7 . Concordantly, the postprandial rise in glucose in response to identical meals was more pronounced in the morning compared with later in the day in insulin‐naïve individuals with type 2 diabetes 8 .…”
Section: Discussionsupporting
confidence: 83%
“…The inferior postprandial glucose control and higher insulin doses after breakfast compared with lunch and dinner suggest that breakfast poses greater challenges to automated systems. A similar pattern with higher excursions after breakfast compared with lunch was observed in previous work exploring fully closed‐loop insulin delivery in adults with type 2 diabetes in a controlled research setting 7 . Concordantly, the postprandial rise in glucose in response to identical meals was more pronounced in the morning compared with later in the day in insulin‐naïve individuals with type 2 diabetes 8 .…”
Section: Discussionsupporting
confidence: 83%
“…Similar findings were observed in individuals with type 1 diabetes 3 . In patients with type 2 diabetes, we have previously shown that fully automated closed‐loop insulin delivery using FA versus IAsp resulted in similar glucose control with 10% more insulin delivered (an additional 3.7 U was delivered with FA, P = .021) 4 . We further demonstrated that FA reached maximal insulin concentrations approximately 15 min earlier than IAsp 5 .…”
Section: Introductionsupporting
confidence: 80%
“…3 In patients with type 2 diabetes, we have previously shown that fully automated closed-loop insulin delivery using FA versus IAsp resulted in similar glucose control with 10% more insulin delivered (an additional 3.7 U was delivered with FA, P = .021). 4 We further demonstrated that FA reached maximal insulin concentrations approximately 15 min earlier than IAsp. 5 Differences in the pharmacological profile and delivery of exogenous insulin may affect other determinants of glucose homeostasis.…”
Section: Introductionmentioning
confidence: 52%
“…Furthermore, as the system only requires the user's body weight for initialization, the burden on the patients and effect on daily activities are minimal. Faster aspart has been previously investigated in fully closedloop systems [19,[24][25][26]; however, in these studies, the insulin dosing algorithm of the device was not optimized with the PK profile of faster aspart. Another strength of the current study is the crossover study design, which allowed the evaluation of within-participant t max settings, thereby reducing the impact of inter-participant variability.…”
Section: Discussionmentioning
confidence: 99%